2005
DOI: 10.1038/sj.ijo.0803079
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue and metabolic effects: new insight into measurements

Abstract: BACKGROUND: Epidemiologic evidence supports the theory that the relation between obesity and disease risk begins early in life, and those risk factors for disease track, or remain at a similar level, with advancing age, growth, and development. The fat tissue, once considered as a depot for energy substrate, is a metabolically active tissue. The fat cells produce agents that regulate a host of physiological processes directly related to carbohydrate and fat metabolism and the development of cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
1
32
1
1
Order By: Relevance
“…In research, the investigation of the association between early growth data and later outcomes is desirable. 23 The determination of where a subject is in the continuum of puberty is complicated. Inferring pubertal stage from chronological age is an unreliable method because of the physiological discrepancy between chronological and biological age at this time of life.…”
Section: Using the Correct Measurementsmentioning
confidence: 99%
“…In research, the investigation of the association between early growth data and later outcomes is desirable. 23 The determination of where a subject is in the continuum of puberty is complicated. Inferring pubertal stage from chronological age is an unreliable method because of the physiological discrepancy between chronological and biological age at this time of life.…”
Section: Using the Correct Measurementsmentioning
confidence: 99%
“…Epidemiological studies have shown that, already in childhood, abdominal fat appears to be significantly associated with an unfavorable metabolic profile, including insulin resistance, decreased high-density lipoprotein-and elevated low-density lipoprotein-cholesterol concentrations and high concentrations of triacylglycerol (Brambilla et al, 1994;Gower et al, 1998;Freedman et al, 1999;Goran and Gower, 1999;Teixeira et al, 2001;Pietrobelli et al, 2005). Although it has been suggested that subcutaneous abdominal adipose tissue (SAAT) is independently associated with insulin resistance (Goran and Gower, 1999), most research suggests that SAAT has a protective effect on metabolic risk (Weiss and Caprio, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…42 Recently, the relation between both macro-(low fat vs low carbohydrate) and micro (ie, calcium, iron) nutrients intake and childhood obesity has been discussed for both the treatment and the development of obesity. 43 Despite the sense of this relationship it is not well established; it is important to optimize the nutritional status from fetal life to adolescence.…”
Section: Metabolismmentioning
confidence: 99%